The Macroeconomic Consequences of EMU: International Evidence from a DSGE Model - Oke Röhe; Jürgen Jerger (Verein für Socialpolitik, 2010)
In this paper, we estimate a New Keynesian DSGE model developed by Ireland (2003) on French, German and Spanish data with the aim to explore the macroeconomic consequences of EMU. In order to validate the results from the DSGE model, we amend this analysis by stability tests of monetary policy reaction functions for these countries. We find that (a) the DSGE structure is well suited for the characterization of key macroeconomic features of the three economies; (b) significant efficiency gains were realized in terms of lower adjustment cost of prices and the capital stock; (c) the behavior of monetary policy did not change in Germany, unlike in France and Spain. Specifically, the impact of inflation on interest rates increased considerably in the two latter countries.
Keywords: E31; E32; E52; 330; DSGE; Monetary Policy; EMU